Long-term damage from the Great Recession in OECD countries - Laurence Ball (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2014)
This paper estimates the long-term effects of the global recession of 2008–2009 on output in 23 countries. I measure these effects by comparing current estimates of potential output from the OECD and IMF to the path that potential was following in 2007, according to estimates at the time. The losses in potential output range from almost nothing in Australia and Switzerland to more than 30 percent in Greece, Hungary, and Ireland; the average loss, weighted by economy size, is 8.4 percent. Most countries have experienced strong hysteresis effects: shortfalls of actual output from pre-recession trends have reduced potential output almost one-for-one. In the hardest-hit economies, the current growth rate of potential is depressed, implying that the extent of lost potential is growing over time.
Keywords: E32; E65; E66; 330; Great Recession; hysteresis; potential output